“Never Trust a Survivor”: Historical Trauma, Postmemory and the Armenian Genocide in Kurt Vonnegut’s Bluebeard - Piechucka, Alicja (Text Matters: A Journal of Literature, Theory and Culture, 2021)
The article focuses on Kurt Vonnegut’s lesser-known and underappreciated 1987 novel Bluebeard, which is analyzed and interpreted in the light of Marianne Hirsch’s seminal theory of postmemory. Even though it was published prior to Hirsch’s formulation of the concept, Vonnegut’s novel intuitively anticipates it, problematizing the implications of inherited, second-hand memory. To further complicate matters, Rabo Karabekian, the protagonist-narrator of Bluebeard, a World War II veteran, amalgamates his direct, painful memories with those of his parents, survivors of the Armenian Genocide. Both the novel and the theory applied to it centre on the problematics of historical and personal trauma, engendered by two genocides which are often the object of comparative analyses: the Armenian Genocide, also referred to as the Armenian Holocaust, and the Jewish Holocaust. The latter is central to Hirsch’s interdisciplinary work in the field of memory studies, encompassing literature, the visual arts and gender studies. In Bluebeard, Vonnegut holds to account a humanity responsible for the atrocities of twentieth-century history: two world wars and two genocides for which they respectively established the context. The article examines the American writer’s reflection on death and violence, man’s destructive impulse and annihilation. In a world overshadowed by memories of mass extermination, Vonnegut interrogates the possibility of a new beginning, pointing to women as agents of renewal and sociopolitical change. He also identifies the role that art plays in the process of potential reconstruction, the story of Karabekian, a failed artist and highly successful art collector, being a Künstlerroman with a feminist edge.